0
$\begingroup$

\begin{align*} \left( \begin{array}{ccc|ccc} 3 & -2 & 2 & 1 & 0 & 0 \\ -2 & 3 & -2 & 0 & 1 & 0 \\ 2 & -2 & 3 & 0 & 0 & 1 \end{array} \right) &\xrightarrow{S_2 \to S_2 + S_3} \left( \begin{array}{ccc|ccc} 3 & 0 & 2 & 1 & 0 & 0 \\ -2 & 1 & -2 & 0 & 1 & 0 \\ 2 & 1 & 3 & 0 & 0 & 1 \end{array} \right) \\ &\xrightarrow{Z_2 \to Z_2 + Z_3} \left( \begin{array}{ccc|ccc} 3 & 0 & 2 & 1 & 0 & 0 \\ 0 & 2 & 1 & 0 & 1 & 1 \\ 2 & 1 & 3 & 0 & 0 & 1 \end{array} \right) \\ &\xrightarrow{S_3 \to S_3 - \frac{2}{3} S_1} \left( \begin{array}{ccc|ccc} 3 & 0 & 0 & 1 & 0 & 0 \\ 0 & 2 & 1 & 0 & 1 & 1 \\ 2 & 1 & \frac{5}{3} & 0 & 0 & 1 \end{array} \right) \\ &\xrightarrow{Z_3 \to Z_3 - \frac{2}{3} Z_1} \left( \begin{array}{ccc|ccc} 3 & 0 & 0 & 1 & 0 & 0 \\ 0 & 2 & 1 & 0 & 1 & 1 \\ 0 & 1 & \frac{5}{3} & -\frac{2}{3} & 0 & 1 \end{array} \right) \\ &\xrightarrow{S_3 \to S_3 - \frac{1}{2} S_2} \left( \begin{array}{ccc|ccc} 3 & 0 & 0 & 1 & 0 & 0 \\ 0 & 2 & 0 & 0 & 1 & 1 \\ 0 & 1 & \frac{7}{6} & -\frac{2}{3} & 0 & 1 \end{array} \right) \\ &\xrightarrow{Z_3 \to Z_3 - \frac{1}{2} Z_2} \left( \begin{array}{ccc|ccc} 3 & 0 & 0 & 1 & 0 & 0 \\ 0 & 2 & 0 & 0 & 1 & 1 \\ 0 & 0 & \frac{7}{6} & -\frac{2}{3} & -\frac{1}{2} & \frac{1}{2} \end{array} \right). \end{align*}

Es gilt also $$ \begin{pmatrix} 1 & 0 & 0 \\ 0 & 1 & 1 \\ -\frac{2}{3} & -\frac{1}{2} & \frac{1}{2} \end{pmatrix} \begin{pmatrix} 3 & -2 & 2 \\ -2 & 3 & -2 \\ 2 & -2 & 3 \end{pmatrix} \begin{pmatrix} 1 & 0 & -\frac{2}{3} \\ 0 & 1 & -\frac{1}{2} \\ 0 & 1 & \frac{1}{2} \end{pmatrix} = \begin{pmatrix} 3 & 0 & 0 \\ 0 & 2 & 0 \\ 0 & 0 & \frac{7}{6} \end{pmatrix}. $$

(Original image here.)

Could someone please explain or give me a hint in the right direction as to what method is being used to diagonalize this matrix.

I understand that performing these operations is equivalent to multiplying with an elementary matrix so we want to them simultaneously with the identity matrix.

I dont quite understand the logic behind the first step and why the result at the end holds.

$\endgroup$
  • $\begingroup$ The picture doesn't make it clear. The method seems to be finding a basis of eigenvectors corresponding to distinct eigenvalues. When a symmetric matrix has two eigenvectors corresponding to distinct eigenvalues, they are necessarily orthogonal. Then it is very easy to use that basis to produce a diagonal matrix, similiar to the original symmetric matrix. $\endgroup$ – hardmath Jun 18 '18 at 15:46
  • $\begingroup$ I forgot to mention, the goal is not only to find a diagonal matrix that is similar but one so that A=Q^t *D * Q $\endgroup$ – fibo11235 Jun 18 '18 at 15:48
  • $\begingroup$ Yes, this is what we usually mean by "diagonalizing a (real) symmetric matrix". The orthogonality of a basis of eigenvectors makes it straightforward to construct the orthogonal matrix $Q$ that accomplishes a "change of basis". $\endgroup$ – hardmath Jun 18 '18 at 15:50
  • $\begingroup$ The procedure is, I think, a bit misleading for diagonalization. It requires us to know in advance what the three eigenvalues are and that they are distinct (in this case $3,2,7/6$). In other words, we know the destination we want to drive the elimination procedure to from some considerations not shown in the picture. $\endgroup$ – hardmath Jun 18 '18 at 16:06
  • 1
    $\begingroup$ @hardmath: This method does not diagonalize $A$ as an endomorphism, but as a bilinear form: The values 3, 2, 7/6 are not (necessarily) the eigenvalues of $A$, and the resulting matrix on the right is not (necessarily) orthogonal. No additional information about $A$ is nedded for this procedure. $\endgroup$ – Jendrik Stelzner Jun 18 '18 at 19:16
1
$\begingroup$

Algorithm discussed at http://math.stackexchange.com/questions/1388421/reference-for-linear-algebra-books-that-teach-reverse-hermite-method-for-symmetr
https://en.wikipedia.org/wiki/Sylvester%27s_law_of_inertia
$$ H = \left( \begin{array}{rrr} 3 & - 2 & 2 \\ - 2 & 3 & - 2 \\ 2 & - 2 & 3 \\ \end{array} \right) $$ $$ D_0 = H $$ We choose a sequence of elementary matrices $E_j$ and perform steps: $$ E_j^T D_{j-1} E_j = D_j $$ $$ P_{j-1} E_j = P_j $$ $$ E_j^{-1} Q_{j-1} = Q_j \; , $$ which maintain: $$ P_j Q_j = Q_j P_j = I $$ $$ P_j^T H P_j = D_j $$ $$ Q_j^T D_j Q_j = H $$

$$ H = \left( \begin{array}{rrr} 3 & - 2 & 2 \\ - 2 & 3 & - 2 \\ 2 & - 2 & 3 \\ \end{array} \right) $$

==============================================

$$ E_{1} = \left( \begin{array}{rrr} 1 & \frac{ 2 }{ 3 } & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \\ \end{array} \right) $$ $$ P_{1} = \left( \begin{array}{rrr} 1 & \frac{ 2 }{ 3 } & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \\ \end{array} \right) , \; \; \; Q_{1} = \left( \begin{array}{rrr} 1 & - \frac{ 2 }{ 3 } & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \\ \end{array} \right) , \; \; \; D_{1} = \left( \begin{array}{rrr} 3 & 0 & 2 \\ 0 & \frac{ 5 }{ 3 } & - \frac{ 2 }{ 3 } \\ 2 & - \frac{ 2 }{ 3 } & 3 \\ \end{array} \right) $$

==============================================

$$ E_{2} = \left( \begin{array}{rrr} 1 & 0 & - \frac{ 2 }{ 3 } \\ 0 & 1 & 0 \\ 0 & 0 & 1 \\ \end{array} \right) $$ $$ P_{2} = \left( \begin{array}{rrr} 1 & \frac{ 2 }{ 3 } & - \frac{ 2 }{ 3 } \\ 0 & 1 & 0 \\ 0 & 0 & 1 \\ \end{array} \right) , \; \; \; Q_{2} = \left( \begin{array}{rrr} 1 & - \frac{ 2 }{ 3 } & \frac{ 2 }{ 3 } \\ 0 & 1 & 0 \\ 0 & 0 & 1 \\ \end{array} \right) , \; \; \; D_{2} = \left( \begin{array}{rrr} 3 & 0 & 0 \\ 0 & \frac{ 5 }{ 3 } & - \frac{ 2 }{ 3 } \\ 0 & - \frac{ 2 }{ 3 } & \frac{ 5 }{ 3 } \\ \end{array} \right) $$

==============================================

$$ E_{3} = \left( \begin{array}{rrr} 1 & 0 & 0 \\ 0 & 1 & \frac{ 2 }{ 5 } \\ 0 & 0 & 1 \\ \end{array} \right) $$ $$ P_{3} = \left( \begin{array}{rrr} 1 & \frac{ 2 }{ 3 } & - \frac{ 2 }{ 5 } \\ 0 & 1 & \frac{ 2 }{ 5 } \\ 0 & 0 & 1 \\ \end{array} \right) , \; \; \; Q_{3} = \left( \begin{array}{rrr} 1 & - \frac{ 2 }{ 3 } & \frac{ 2 }{ 3 } \\ 0 & 1 & - \frac{ 2 }{ 5 } \\ 0 & 0 & 1 \\ \end{array} \right) , \; \; \; D_{3} = \left( \begin{array}{rrr} 3 & 0 & 0 \\ 0 & \frac{ 5 }{ 3 } & 0 \\ 0 & 0 & \frac{ 7 }{ 5 } \\ \end{array} \right) $$

==============================================

$$ P^T H P = D $$ $$\left( \begin{array}{rrr} 1 & 0 & 0 \\ \frac{ 2 }{ 3 } & 1 & 0 \\ - \frac{ 2 }{ 5 } & \frac{ 2 }{ 5 } & 1 \\ \end{array} \right) \left( \begin{array}{rrr} 3 & - 2 & 2 \\ - 2 & 3 & - 2 \\ 2 & - 2 & 3 \\ \end{array} \right) \left( \begin{array}{rrr} 1 & \frac{ 2 }{ 3 } & - \frac{ 2 }{ 5 } \\ 0 & 1 & \frac{ 2 }{ 5 } \\ 0 & 0 & 1 \\ \end{array} \right) = \left( \begin{array}{rrr} 3 & 0 & 0 \\ 0 & \frac{ 5 }{ 3 } & 0 \\ 0 & 0 & \frac{ 7 }{ 5 } \\ \end{array} \right) $$ $$ Q^T D Q = H $$ $$\left( \begin{array}{rrr} 1 & 0 & 0 \\ - \frac{ 2 }{ 3 } & 1 & 0 \\ \frac{ 2 }{ 3 } & - \frac{ 2 }{ 5 } & 1 \\ \end{array} \right) \left( \begin{array}{rrr} 3 & 0 & 0 \\ 0 & \frac{ 5 }{ 3 } & 0 \\ 0 & 0 & \frac{ 7 }{ 5 } \\ \end{array} \right) \left( \begin{array}{rrr} 1 & - \frac{ 2 }{ 3 } & \frac{ 2 }{ 3 } \\ 0 & 1 & - \frac{ 2 }{ 5 } \\ 0 & 0 & 1 \\ \end{array} \right) = \left( \begin{array}{rrr} 3 & - 2 & 2 \\ - 2 & 3 & - 2 \\ 2 & - 2 & 3 \\ \end{array} \right) $$

$\endgroup$
0
$\begingroup$

Any real symmetric matrix $A \in \operatorname{M}_n(\mathbb{R})$ is congruent to a diagonal matrix $D \in \operatorname{M}_n(\mathbb{R})$, i.e. therere exists an invertible matrix $S \in \operatorname{GL}_n(\mathbb{R})$ with $S A S^T = D$. This is a matrix version of the fact that for every symmetric bilinear form $\beta \colon V \times V \to \mathbb{R}$ on a finite dimensional real vector space $V$ there exists a basis of $V$ which is orthogonal with respect to $\beta$.

One can find such matrices $D$ and $S$ by using simultaneous column and row operations:

  • We apply an elementary column operation to $A$, resulting in a matrix $A'$. The matrix $A'$ will (in most cases) not be symmetric again.

  • To fix this we then apply the corresponding elementary row operation to $A'$, resulting in a matrix $B$. The matrix $B$ is then again symmetric.

By repeatedly applying the above two steps we bring $A$ into a lower triangular form (similar to how the Gauß algorithm brings a matrix into row echolon form). Because the matrix stays symmetric throughout this process (after applying both column and row operations), the resulting symmetric matrix $D$ will also be upper tringular, and therefore a diagonal matrix.

A suitable invertible matrix $S$ with $S A S^T = D$ can then be calculated by applying the the elementry row operations from above in the same order to the identity matrix.

Instead of first calculating $D$ and then $S$, one can also calculate both at the same time, by applying to the elementary row operations to both $D$ and $S$ at the same time. (This is similar to computing the inverse of a matrix $A \in \operatorname{GL}_n(K)$ via the Gauß-algorithm, by transforming $A$ to the identity matrix via elementary row operations while simultaneously applying the same row operations to the identity matrix $I$ to calculate $A^{-1}$.) This is precisely what is done in your example:

  • In the first iteration, the third column is added to the second column. Thus we get $(A \mid I) \to (A' \mid I)$ with $A'$ not being symmetric.

  • We now apply the corresponding elementary row operation to both matrices, adding the third row to the second row. We get $(A' \mid I) \to (B \mid Q)$. Note that $B$ is again symmetric and that $Q A Q^T = B$.

  • In the second iteration, we substract $2/3$-times the first column from the third column. We get $(B \mid Q) \to (B' \mid Q)$ with $B'$ not being symmetric.

  • We now apply the corresponding elementary row operation to both matrices, subtracting $2/3$-times the first row from the third row. We get $(B' \mid Q) \to (C \mid R)$. Note that $C$ is again symmetric and that $R A R^T = C$.

  • In the third iteration, we subtract half of the second column from the third column. We get $(C \mid R) \to (C' \mid R)$ with $C'$ not being symmetric.

  • Now we apply the corresponding elementary row operation to both matrices, subtracting half of the second row from the third row. We get $(C' \mid R) \to (D \mid S)$. Note that $D$ is again symmetric and that $S A S^T = S$.

Since $D$ is also diagonal the algorithm terminates.

An explanation of this algorithm can be found in Gerd Fischer’s Lineare Algebra, section 5.7.6 (the book is in German), and a similar overview as above can be found in these notes, section 6.2 (also in German).

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.